Place Your Bets? The Value of Investment Research on Reddit’s Wallstreetbets - Bradley, Daniel; Hanousek, Jan; Jame, Russell; Xiao, Zicheng (Review of Financial Studies, 2024)
Abstract We examine the value of due diligence recommendations on Reddit’s Wallstreetbets (WSB) platform. Before the Gamestop (GME) short squeeze, recommendations are significant predictors of returns and cash-flow news. This predictability is eliminated post-GME. Post-GME, the fraction of reports emphasizing price-pressure or attention-grabbing stocks dramatically increases, and the decline in informativeness is concentrated in these reports. Similarly, retail trade informativeness is particularly strong following DD reports in the pre-GME period, but not post-GME. Our findings are consistent with the view that the Gamestop event altered the culture of WSB, leading to a deterioration in investment quality that adversely affected smaller investors.